Análisis de la Planta turística, oferta alojamiento del cantón Sigchos - Pinzón Colmenares, Jenifer Alejandra (2021)
The present research project was carried out in the Sigchos canton of the province of Cotopaxi, where the tourist plant and lodging supply were analyzed and updated data were obtained. The first specific objective was based on the execution of the situational diagnosis through a bibliographic review and the analytical method. The 2015 Territorial Development and Management Plan was also considered, resulting in the compilation of information by four main axes: social, economic, environmental and tourism. The tourism demand in the canton is 25,920 tourists per year, and its main attractions are the Quilotoa Lagoon and the Toachi Canyon. The second objective was to conduct an inventory of the lodging supply by means of technical sheets, field research, interviews with officials of the Sigchos Municipal Government and the staff of the different lodging establishments. The study identified 17 lodging establishments: 7 hostels, 3 inns, 1 tourist camp and 6 establishments that do not appear in the tourism cadastre; these establishments offer a variety of services depending on their category and are located in three parishes: Sigchos, Chugchilán and Isinliví. The third objective was to develop a tourism catalog using techniques and tools such as: computer, cell phone and the CANVA application. All the information of each establishment was also recorded and divided into three parts: front cover, content and back cover. In addition, the title, author, year, place, category, address, telephone numbers, infrastructure, services, location, prices and photographs were established; the catalog will serve as an informative tool of the tourist plant, lodging offer of the Sigchos canton.